2016
DOI: 10.1088/2057-1976/2/5/055011
|View full text |Cite
|
Sign up to set email alerts
|

A new solution for radiation transmission in anti-scatter grids

Abstract: Analytic calculations of radiation transmission in focused grids or parallel grids are currently performed using the Day and Dance method. In parallel grids, this method calculates the mean transmission of radiation of grid units each of which consists of a strip and the adjacent interspace. The Day and Dance method extrapolates grid-unit-mean transmission of uniformly distributed radiation in focused grids and may underestimate the transmission of scatter radiation. This method fails to preserve detailed grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 55 publications
8
21
0
2
Order By: Relevance
“…Results from previous simulation investigations 13,17 showed that radiation transmissions in grids were affected by the virtual image receptors stimulated with a physical image receptor without all the construction details. In both the grid evaluation and the determination of SPR, this work necessitated the use of a simulated perfectly efficient detector of energy‐integration to avoid any potential bias from the construction of a physical image receptor.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Results from previous simulation investigations 13,17 showed that radiation transmissions in grids were affected by the virtual image receptors stimulated with a physical image receptor without all the construction details. In both the grid evaluation and the determination of SPR, this work necessitated the use of a simulated perfectly efficient detector of energy‐integration to avoid any potential bias from the construction of a physical image receptor.…”
Section: Methodsmentioning
confidence: 96%
“…In this work, the simulation included the interference effect on Rayleigh scattering which has an effect on scatter‐to‐primary ratio (SPR) 13,29,32–35 and Ts 13,35,36 . The simulation of radiation transport in the grid materials were performed using the method of Zhou et al 17 in which the interaction probability of each photon in the grid materials was determined by the path lengths in each type of grid materials. These path lengths were presumably determined as if the photon would traverse the grid materials without an interaction with them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As modificações no código que envolviam a dosimetria da mama foram validadas ao comparar os resultados do Report TG-195 22 , Nosratieh et al 31 , Sarno et al 9 e Wu et al 5 . O algoritmo da grade antiespalhamento foi validado previamente 32 comparando os resultados de Zhou et al 33 e Cunha et al 7 3. Resultados e Discussão 3.1.…”
Section: Validação Do Códigounclassified
“…Several degrading mechanisms exist, including patient voluntary and involuntary motion, detector blur, inferior detective quantum efficiency (DQE) and scatter radiations amongst others. Scatter radiation being the dominant image degradation mechanism, many researchers have investigated hardware based scatter correction methods that currently refer to the use of antiscatter grids (Fetterly and Schueler 2008, Carton et al 2009, Zhou et al 2016, Omondi et al 2020. However, the scatter correction efficacy of anti-scatter grids needs further improvements by improving the grid designs based on the fundamental grids features that include, grid ratio (r), grid frequency (N) and septa to interspace ratio (R) amongst others (Zhou et al 2020).…”
Section: Introductionmentioning
confidence: 99%